Lateral Temporal Bone Resection in Advanced Cutaneous Squamous Cell Carcinoma: Report of 35 Patients - Essig, Garth F.; Kitipornchai, Leon; Adams, Felicity; Zarate, Dannie; Gandhi, Mitesh; Porceddu, Sandro; Panizza, Benedict (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objective To evaluate lateral temporal bone resection (LTBR) in the management of advanced cutaneous squamous cell carcinoma (SCC) with temporal bone invasion and patterns of failure.Methods This is a retrospective study of 35 patients undergoing lateral temporal bone resection for advanced cutaneous SCC at a tertiary care center between 1995 and 2006.Results The Pittsburgh tumor stage was T4 in 18 patients (51%), T3 in 5 (14%), T2 in 9 (26%), and T1 in 3 (9%). Clear margins were reported in 22 (63%) patients. Resection of the mandible and/or temporomandibular joint (TMJ) was required in 11 (31%) patients. Facial nerve involvement was seen in 10 (29%) patients. Survival outcomes at 2 and 5 years for overall survival were 72% and 49%; disease-free survival, 68% and 59%; and disease-specific survival, 79% and 62%, respectively. Pittsburgh T stage correlated significantly with disease-specific survival (p = 0.015) and margin status was significant for both disease-free survival (p = 0.0015) and disease-specific survival (p < 0.001).Conclusions Surgery with curative intent is justified for cutaneous SCC invading the temporal bone with extended LTBR. Margin status was a significant predictor of outcome. Surgeons should plan preoperatively to achieve clear margins by extending the LTBR with possible nerve resection.
Keywords: temporal bone; cutaneous malignancy; squamous cell carcinoma; temporal bone resection